The Analysis of Loosening of Bolt Connection Due to Structural Vibration Through Changes in Dynamic Characteristics - Rahmatsyah Maksum Ramsi; Meifal Rusli; Mulyadi Bur (Jurnal Teknik Mesin, 2023)
Bolted joints are generally used to connect two or more mechanical structures due to their ease of assembly and disassembly for maintenance. However, the problem of vibration is one of the main challenges when the tightness of the bolted joints is insufficient, causing failures such as looseness and resulting in disconnection. Looseness is the most common cause of dynamically loaded bolted joint structure failure. This study tested a simple bolt joint structure to observe the looseness indication of the bolt joint after it was vibrated using a shaker in a single-frequency excitation. A freely fixed beam consisting of two beams connected by a bolt and subjected to varying bolt tightening torques. Then the response measurement is carried out by recording the FRF graph obtained from loosening and tightening bolt torque effects. Modal parameters such as personal frequency and damping ratio were collected through experimental modal analysis (EMA). It was found that the structure’s vibration could change the conditions of loosening or lower tightening torque indicated by shifting the structure’s natural frequency. In addition, the damping characteristics are also affected by changes in the tightening torque. Especially when conditions are loose, the damping ratio becomes much higher than that of tightening.